Helsinkiläisiä puhujaprofiileja - Paunonen, Heikki (Virittäjä, 2005)
Speech profiles of Finnish speakers in Helsinki (englanti) 2/2005 (109) Speech profiles of Finnish speakers in Helsinki By analysing the speech profiles of individual speakers, the article looks at the changes that have occurred in the Finnish spoken in Helsinki since the early twentieth century. The Finnish spoken in Helsinki today began to take shape well over a century ago. At that time, two separate traditions were evident: one was the language spoken by working people who had moved to Helsinki from rural areas, which was initially very dialect-based, and the other was the almost literary Finnish spoken by young educated Finnish-speakers. The contrast between the literary spoken language of the intelligentsia and the dialectal language of the working population was at its greatest during the late nineteenth and early twentieth centuries. The study uses two extensive sets of interview data collected in Helsinki, one from 1972-1974 and the other from 1991-1992. The informants were men and women from two different parts of the city and represent three different social groups and three different age groups. The 1970s data comprises recordings of 149 informants, and 96 of these were selected for the study. The 1990s recordings included 29 of the people interviewed in the 1970s and a further 16 younger informants. The writer takes a closer look at the most typical Helsinki speakers in each of the two datasets. A speech profile was drawn up for every informant, based on 25 language characteristics. The characteristics used were those that would allow the contrast between the literary and originally dialect-based forms of spoken Finnish to be ascertained as clearly as possible. Diagrams are given showing the literary variant unshaded and the other variant shaded. The speech profiles of the speakers were examined from three viewpoints. Firstly, the 1970s speakers, all with different backgrounds, were compared with each other. Secondly, corresponding generations of speakers from the 1970s and 1990s were compared, and thirdly, the 1970s and 1990s profiles of the same speakers were compared. Special attention was focused on those with an academic education and on children of parents with an academic education. The analysis of the 1970s data revealed that among the oldest speakers there were still those who spoke very literary Finnish and those who spoke very dialectal Finnish. In the case of the speaker with the strongest literary Finnish, the proportion of colloquial speech was 0%. Among middle-aged informants with an academic education there were also those who still spoke fairly literary Finnish. The younger speakers, however, differed very considerably both from the elderly and middle-aged informants. Even the young person with the most literary Finnish used colloquial speech 78% of the time. The change has been nothing less than dramatic. The generational comparison demonstrated a very marked difference between elderly speakers with an academic education in the 1970s and in the 1990s: in the 1970s data their speech was very literary, but in the 1990s data there were no longer any speakers of literary Finnish. Comparison of the speakers who appeared in both the 1970s and 1990s datasets showed that even the language of middle-aged speakers has, in certain cases, changed in 20 years, with some of them becoming more colloquial and some more literary. Similarly, the speech of one of the young informants from the 1970s has become more literary, while for another it has become more colloquial. The changes that have occurred in spoken Finnish in Helsinki have also been reflected in the language used in formal situations. The language previously spoken in official contexts, such as in administration, teaching and the mass media, was very literary. Over the past few decades, however, the language spoken in formal situations has changed and now increasingly features language that was at first characteristic of younger speakers. Heikki Paunonen